Effects of uniaxial stress on dielectric properties of lithium modified potassium sodium niobate ceramics - S. Wongsaenmai (2018)
In this work, the solid solution of ((K0.5Na0.5)1-xLix)NbO3ceramics with x=0.03, 0.04, 0.05, 0.06 and 0.07 was prepared by a conventional mixed-oxide and solid-state sintering method. The structural phase formation and microstructure were characterized by X-ray diffraction technique and scanning electron microscopy. The ceramics were identified by XRD as a single-phase perovskite structure with symmetry gradually changing from orthorhombic to tetragonal. The grain size and the optimum density of the sintered ceramics were noticeably compositional-dependent. The dielectric properties of the ((K0.5Na0.5)1-xLix)NbO3ceramics under the uniaxial compressive stress were observed at stress up to 180 MPa. The results showed that the dielectric constant and the dielectric loss tangent increased with applied stress. The change in the dielectric properties with stress was seen to depend on the composition and grain size. The observations were interpreted in terms of the intrinsic and extrinsic contributions to the changes in dielectric properties upon the applied compressive stress. © 2011 Elsevier B.V. All rights reserved.